2015
DOI: 10.1039/c5cc05985b
|View full text |Cite
|
Sign up to set email alerts
|

An azobenzene-containing metal–organic framework as an efficient heterogeneous catalyst for direct amidation of benzoic acids: synthesis of bioactive compounds

Abstract: An azobenzene-containing zirconium metal-organic framework was demonstrated to be an effective heterogeneous catalyst for the direct amidation of benzoic acids in tetrahydrofuran at 70 °C. This finding was applied to the synthesis of several important, representative bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…24 A recent catalytic study reported an acetic acid (525 equivalents) modulated synthesis of Zr-L7 that resulted in micron-sized particles. 30 Isolation of discrete octahedral single crystals of Zr-L7 and Zr-L8 was possible using four equivalents of L-proline and one equivalent of HCl in a solvothermal synthesis at 100 C for 48 h in DMF. During repeated syntheses, it was noted that order of addition was key to gaining large single crystals; addition of HCl to a pre-sonicated mixture of the other reagents provided optimal results.…”
Section: Resultsmentioning
confidence: 99%
“…24 A recent catalytic study reported an acetic acid (525 equivalents) modulated synthesis of Zr-L7 that resulted in micron-sized particles. 30 Isolation of discrete octahedral single crystals of Zr-L7 and Zr-L8 was possible using four equivalents of L-proline and one equivalent of HCl in a solvothermal synthesis at 100 C for 48 h in DMF. During repeated syntheses, it was noted that order of addition was key to gaining large single crystals; addition of HCl to a pre-sonicated mixture of the other reagents provided optimal results.…”
Section: Resultsmentioning
confidence: 99%
“…Theb ackswitching is driven by visible light illumination or thermal relaxation. [11,12] These efforts can be divided into three groups depending on whether the azobenzene moiety is accommodated as 1) the actual framework linker, [13,14] 2) as ide-group pendant to the linker, [15,16] or 3) ag uest species in the pores incorporated either during the synthesis or through ap ostsynthesis treatment. [11,12] These efforts can be divided into three groups depending on whether the azobenzene moiety is accommodated as 1) the actual framework linker, [13,14] 2) as ide-group pendant to the linker, [15,16] or 3) ag uest species in the pores incorporated either during the synthesis or through ap ostsynthesis treatment.…”
mentioning
confidence: 99%
“…[9,10] Introduction of azobenzene moieties in porous MOF-like materials has already been challenged in recent studies. [11,12] These efforts can be divided into three groups depending on whether the azobenzene moiety is accommodated as 1) the actual framework linker, [13,14] 2) as ide-group pendant to the linker, [15,16] or 3) ag uest species in the pores incorporated either during the synthesis or through ap ostsynthesis treatment. [17,18] Thef irst alternative would be truly exciting but difficult to realize;t he challenges arise from the fact that azobenzene is an integral part of ar igid crystal structure in which the trans-cis transformation either does not occur owing to the lack of free space,o ro ccurs but destroys the crystal lattice in an irreversible manner.…”
mentioning
confidence: 99%
“…Introduction of azobenzene moieties in porous MOF‐like materials has already been challenged in recent studies . These efforts can be divided into three groups depending on whether the azobenzene moiety is accommodated as 1) the actual framework linker, 2) a side‐group pendant to the linker, or 3) a guest species in the pores incorporated either during the synthesis or through a post‐synthesis treatment . The first alternative would be truly exciting but difficult to realize; the challenges arise from the fact that azobenzene is an integral part of a rigid crystal structure in which the trans – cis transformation either does not occur owing to the lack of free space, or occurs but destroys the crystal lattice in an irreversible manner …”
Section: Figurementioning
confidence: 99%